A Single institution's randomized double‐armed prospective study of lumpectomy margins with adjunctive use of the MarginProbe in nonpalpable breast cancers. Issue 11 (9th August 2020) - Geha, Rula C.; Taback, Brett; Cadena, Lisa; Borden, Billie; Feldman, Sheldon
Abstract: Breast conservation surgery (BCS) aims to excise all cancerous tissue while minimizing the amount of healthy breast tissue removed. Up to 30% of patients undergoing BCS require a second operation for re‐excision to obtain negative margins. Previous studies reported a lower re‐excision rate with intraoperative use of the MarginProbe device (Dune Medical Devices). This device utilizes radiofrequency spectroscopy to detect differences between cancerous and normal tissue. From July 2009 to January 2010, our institution enrolled 46 patients electing for BCS in a prospective double‐arm randomized controlled trial and had a significantly lower re‐excision rate than that reported in the multicenter trial. Intraoperatively, after performing conventional lumpectomy with excision of any additional shavings deemed necessary based on palpation and visual inspection alone, patients were then randomized. In the device arm, the surgeon used the MarginProbe to interrogate the lumpectomy specimen, taking additional shavings from the cavity surfaces corresponding to the parts of the specimen read as positive by the device. In the control arm, only standard intraoperative assessments were performed. All specimens were evaluated by pathologists who were blinded to the study arm. In this population, 72% had invasive ductal carcinoma (IDC), 20% had ductal carcinoma in situ (DCIS), and 8% had invasive lobular carcinoma (ILC). Average age was 64 years old. The average size of the specimen was 5.6 cm, the average volume was 37.8 cm 3, and the average weight was 32.7 g. The mean size of DCIS was 1.4 cm. For invasive specimens, 32 were T1 and 7 were T2. Prior to randomization, 43 patients were thought to have positive or close margins and therefore underwent additional shavings. Twenty‐three patients were randomized to the device arm and 23 to the control arm. In the device arm, 14 (60%) patients had IDC, 7 (30%) had DCIS, and 2 (8%) had ILC, vs the control arm where 19 (82%) patients had IDC, 2 (8%) had DCIS, and 2 (8%) had ILC. Eight (35%) patients in the control group vs 1 (4%) in the device group underwent re‐excision for margin involvement ( P  < .05). The use of the MarginProbe device at our institution significantly improved the ability of our surgeons to obtain clear margins during initial BCS. Our results show a lower re‐excision rate (4%) than those published in the multicenter trial (19.8%). We postulate that in the face of more patients having DCIS in our device group (30%), our surgeons responded by taking thicker shavings when the MarginProbe device reported margin involvement during the initial lumpectomy, resulting in greater success achieving clear final margins on the shaved tissue and a significantly lower re‐excision rate than previously reported with the MarginProbe device.